The effect of specific tactical approach exercises to develop the speed and accuracy of the tactical and skillful performance of advanced football players - Ali Majeed Zayer, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The exercises of the tactical approaches used in the research is one of the most important exercises that help the player to perform well in the skill while raising the physical level and enable them to perform the required planning requirements at the same time. The importance of the research appeared in studying the ability of special exercises prepared by the researcher using the method of schematic approaches and their ability to develop physical, skill and planning performance. The problem of the research lies in the failure to give exercises of the tactical approaches in the required form during the training unit, so the researcher proceeded to study this problem by knowing the extent of benefit from the exercises of the style of planning approaches and their impact on the players. The study aimed to prepare exercises for the style of planning approaches to develop the physical, skill and planning performance of the players, as well as to identify their impact on them. The experimental approach was chosen by designing the two equivalent groups (control and experimental) by pre and post measurement method. The research community was identified with players in the governorate of Baghdad, and like the lines club, the research sample, the class of exercises prepared on the experimental group with (3) units per week for a period of (10) weeks. It used a positive effect in developing the skillful and tactical performance of the players, as well as repeating it according to scientific foundations and in a manner similar to the performance that developed the players' performance in terms of accuracy and speed. The researcher recommends the use of exercises for planning approaches, in order to develop the skills and planning side of the players and to develop their teamwork.